ATRT-13. An integrative analysis of the ATRT proteome unravels novel drug targets and refines molecular subgrouping. (3rd June 2022) - Johann, Pascal; Müller, Torsten; Kalxdorf, Mathias; Hasselblatt, Martin; Frühwald, Michael C; Pfister, Stefan M; Krijgsveld, Jeroen; Kool, Marcel
Abstract: INTRODUCTION: Atypical teratoid/rhabdoid tumors (ATRT) represent frequent brain tumors in infants. In recent years, large-scale landscaping efforts on the epigenome and transcriptome of these tumors have unravelled a high degree of heterogeneity and three major molecular subgroups, termed ATRT-TYR, ATRT-SHH, ATRT-MYC, have been identified. The ATRT-proteome, in turn, still represents a largely unchartered territory. METHODS: We have performed a peptide-based screening approach to characterize the proteome of 40 ATRTs and six ATRT cell-lines. All of these samples had matching methylation data available and 28 also corresponding gene expression data. RESULTS: Unsupervised clustering recapitulated the previously described ATRT groups, revealing also a clear split of the SHH-subgroup in a supratentorial (SHH_1) and an infratentorial subgroup (SHH_2). Overall, we identified 7265 proteins, of which 1320 were differentially expressed between the groups, with an enrichment of spliceosome associated terms in SHH_1 and integrins/cell adhesions molecules in SHH_2. ATRT-MYC displayed an overrepresentation of immune cell markers and the TYR subgroup an enrichment of PI3K- as well as mTOR-signaling. Particularly, genes that have previously been described as signature genes for the ATRT-groups such as FABP7 in ATRT-SHH and OTX2 and MITF in ATRT-TYR were among the highly correlating genes that were both expressed in the proteome and the gene expression datasets. On top of this, our analysis revealed highly differentially expressed drug targets such as the tyrosine-kinase MARCKS (overexpressed in ATRT-TYR) not previously identified in ATRT transcriptome data, which warrant investigation by in vitro drug tests. CONCLUSION : Our data reveal the importance of previously described regulatory hubs in the ATRT subgroups, but additionally highlight novel drug targets that merit further exploration. Currently, drug treatment experiments in ATRT cell lines are ongoing to validate these proteins as drug targets, ultimately aiming to establish new therapeutic strategies in this deadly disease.